Free Fatty Acid Induces Endoplasmic Reticulum Stress and Apoptosis of β-cells by Ca(2+)/Calpain-2 Pathways - Cui, Wei (Public Library of Science, 2013)
Dysfunction of β-cells is a major characteristic in the pathogenesis of type 2 diabetes mellitus (T2DM). The combination of obesity and T2DM is associated with elevated plasma free fatty acids (FFAs). However, molecular mechanisms linking FFAs to β-cell dysfunction remain poorly understood. In the present study, we identified that the major endoplasmic reticulum stress (ERS) marker, Grp78 and ERS-induced apoptotic factor, CHOP, were time-dependently increased by exposure of β-TC3 cells to FFA. The expression of ATF6 and the phosphorylation levels of PERK and IRE1, which trigger ERS signaling, markedly increased after FFA treatments. FFA treatments increased cell apoptosis by inducing ERS in β-TC3 cells. We also found that FFA-induced ERS was mediated by the store-operated Ca(2+) entry through promoting the association of STIM1 and Orai1. Moreover, calpain-2 was required for FFA-induced expression of CHOP and activation of caspase-12 and caspase-3, thus promoting cell apoptosis in β-TC3 cells. Together, these results reveal pivotal roles for Ca(2+)/calpain-2 pathways in modulating FFA-induced β-TC3 cell ERS and apoptosis.